Aguinaldo's breakfast and more looking back essays - Ocampo, Ambeth R. (Pasig City, Philippines, 1993)
Collection of articles on Philippines social aspects.
Reader's Knowledge Bookstore MR-BK-2K-04-019G (I-51719)